POSTUR KERJA PADA AKTIVITAS BONGKAR IKAN TUNA DI PELABUHAN PERIKANAN SAMUDERA NIZAM ZACHMAN JAKARTA - Namira Septiani; Mohammad Imron; Fis Purwangka (Jurnal Teknologi Perikanan dan Kelautan, 2022)
The high production of tuna at PPS Nizam Zachman Jakarta increases working time and workload in unloading activities. Tuna unloading activities are manual and involve more than ten workers. On an average day, tuna unloading workers suffer an accident at work and complain of pain in the body caused by non-ergonomic working posture. This study aims to identify work postures in tuna unloading activities and the risks that may arise and identify pain complaints that arise because of tuna unloading activities at PPS Nizam Zachman Jakarta. The method used in this study is the Rapid Entire Body Assessment (REBA) and the Nordic Body Map questionnaire. Based on an assessment using REBA method in the eight stages of the tuna unloading activity has a high-risk level of 62,5%, namely stages where there was an awkward posture while lifting heavy loads. Most of the 85 tuna unloading workers experienced a first complaint rate of 94% on the back and 85% on the waist, a form of musculoskeletal injury due to awkward posture. Recommendations for work postures that can be given to reduce the risk of injury and prevent work accidents use the diagonal lift technique.